Performance assessment, in terms of ripples and power, of conventional and interleaved converter DC–DC with coupled and independent inductors dedicated to photovoltaic installations - Brahim Lagssiyer; Aziz Abdelhak; Mohamed El Hafyani (Institute of Advanced Engineering and Science, 2019)
Our work focuses on the design and analysis of an interleaved Boost converter DC-DC with coupled and independent inductors in terms of ripples and power. An interleaving strategy is adopted to minimize the currents in the Boost components and consequently to miniaturize them. The command shift of the switch by the X.T value (X: shift coefficient 0<X<1 and T: period of the command signal), minimizes the ripple of the input current and output voltage and maximizes the power extracted from the photovoltaic system. The coupling technique of inductances of interleaved Boost, furthermore reduces the ripples of the input currents and further maximizes the power extracted from the photovoltaic panels. To determine the variation of the power extracted from the PV, according to the duty cycle D and the switches command shift X.T, the duty cycle, was manually varied (Similar to a MPPT command). For this we modeled, under MATLAB/Simulink, the photovoltaic system, the power interface (DC/DC Boost interleaved). Finally, a prototype of interleaved Boost converter with coupled inductors and a shifted control of the switches was realized. Experimental results have been proposed to validate the results of simulations.